Enhancing Spatial Literacy through ClassPoint-Integrated Geometry Learning: A Quasi-Experimental StudyType - Suci Frisnoiry; Edy Surya; Tiur Malasari Siregar; Elfitra Elfitra; Sara Frimaulia (Jurnal Ilmu Pendidikan, 2025)
This study evaluates the efficiency of ClassPoint learning media in improving students' spatial literacy in geometry education. Spatial literacy, which includes imagery, reasoning, and communication skills, is crucial for understanding and solving complex geometric problems. The research employed a quasi-experimental methodology, dividing 52 eleventh-grade students into two groups: one utilizing ClassPoint for the experiment and the other employing conventional methods as the control group. We collected data through pretests and posttests with instruments devised particularly to assess three characteristics of spatial literacy. The data analysis included t-tests and N-Gain to evaluate the intervention's effectiveness. The results demonstrated that students in the experimental group showed a significant improvement in spatial literacy compared to the control group. The mean score of the experimental group increased from 66.38 to 85.23 following the intervention, with N-Gain scores for vision at 0.84 (high category), reasoning at 0.81 (high category), and communication at 0.70 (medium category). The interactive features of ClassPoint, such as quizzes, polls, and live annotations, improved the learning experience and aided students' understanding of concepts. This study contributes to educational literature by illustrating the effectiveness of the ClassPoint learning medium in improving spatial literacy in geometry education. This study's practical consequences recommend employing learning tools such as ClassPoint in mathematics lessons to foster a more innovative, engaging, and pertinent educational atmosphere. We expect the results of this study to guide educators and policymakers in developing learning strategies that enhance students' spatial skills development.